Conceptualizing Resistance to Globalization - Chin, Christine B. N.; Mittelman, James H. (Globalization and the Politics of Resistance, 2000)
Assessments of resistance to globalization are necessarily influenced by the manner in which one conceptualizes these processes. Too often, both of the terms (‘resistance’ and ‘globalization’) are used promiscuously, the latter as a buzzword or catchall and the former in many different ways, sometimes as a synonym for challenges, protests, intransigence, or even evasions. Hence, we seek to juxtapose alternative explanations of resistance and highlight the complexities of conceptualizing it. The purpose of this chapter, then, is to explore the question, what is the meaning of resistance in the context of globalization?
Political Science
Keywords: Islamist movement; NAFTA; globalization; international political economy; organic intellectual; resistance; symbolic resource; transnational capital

Market Dominance, Crime, and Globalisation - Messner, Steven F.; Rosenfeld, Richard (Social Dynamics of Crime and Control: New Theories for a World in Transition, 2000)
KM: Our point of departure is Karl Polanyi's classic work on the emergence of industrial capitalism and recent studies that further develop Polanyi's insights. We draw on these analyses to pose a fundamental issue confronting all capitalist societies: the need to restrain the market and prevent the economy from dominating other institutional realms. We explain how this general institutional challenge bear specifically on the problem of crime and crime control
Law
Keywords: crime; double movement; globalization; institutional-anomie theory; law